EDUCATION AS A PRIMARY TOOL OF HUMAN RIGHTS ENFORCEMENT AND NATIONAL DEVELOPMENT - Gibran M. Sanjaya (Universitas Muhammadiyah Metro, 2018)
National development will be well implemented only on a nation with educated people and guaranteed human rights, even further, education is the main crutch in human rights enforcement. However, Indonesia was ranked by PISA as 10 worst of education system from 76 countries, that means alteration of national education system is needed. Considering Indonesia stands before thousands of island and diverse of cultures and religions, the people requires adequate education about the character of their community and their local excellence. The purpose of that should be implemented clearly when look into the current codition of Indonesia, such as urbanization without the decent education from rural society who affect a high social gap. Those things will hamper the national development. The Law No. 20 of 2003 has regulated local content that can increase the education implementation based on local excellence, but the lessons of local content is not different with another lessons that students learn in the class room. Education can’t be interpreted as limited as education which “institutionalized” that take shelter inside the classroom because education is far more than that. Good education should be the core concern of government in order to maximize Indonesia’s national development and capability in global economic.This paper offers to evolve local content in Law No. 20 of 2003 so the people of Indonesia can compete with other countries in facing AEC. The research method that used for this paper is normative-juridical.